2018
DOI: 10.1002/2017jg004360
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Application of Biome‐BGC for Modeling the Daily GPP of Natural Vegetation Over Peninsular Spain

Abstract: A methodology for improving the application of Biome‐BGC in peninsular Spain was developed focusing on the optimization of the rooting depth (zroot), which is not available for the study area on a spatially distributed basis. The optimal zroot was identified by comparing daily gross primary production (GPP) simulations with varying zroot to GPP estimations from a production efficiency model previously optimized for and validated in the study area. The methodology was first tested in four eddy covariance (EC) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Model validation is the process of evaluating the consistency and accuracy of the modeled results relative to field measurements. Biome-BGC has been assessed by performing sensitivity analyses [35] and validations against measured data, including forest [36][37][38], cropland [21], grassland [22,39], and all ecosystems [40]. In this study, we used field data collected from previous studies to evaluate the model's performance in predicting NPP dynamics (as shown in Table 1 for supporting information).…”
Section: Simulation Design and Model Validationmentioning
confidence: 99%
“…Model validation is the process of evaluating the consistency and accuracy of the modeled results relative to field measurements. Biome-BGC has been assessed by performing sensitivity analyses [35] and validations against measured data, including forest [36][37][38], cropland [21], grassland [22,39], and all ecosystems [40]. In this study, we used field data collected from previous studies to evaluate the model's performance in predicting NPP dynamics (as shown in Table 1 for supporting information).…”
Section: Simulation Design and Model Validationmentioning
confidence: 99%
“…Although remote sensing can be used over large areas, the response of grassland ecosystems to grazing cannot be determined because remote sensing images only provide insight into real scenarios. Model simulation combined with observational data is considered the most effective method for studying the spatiotemporal dynamics of the grassland carbon budget and the response to grazing over large areas because it allows different scenarios (e.g., grazed and ungrazed scenarios) to be evaluated in the same region via model estimation (Anh Nguyet and Kawasaki, 2017;Sanchez-Ruiz et al, 2018;Tian et al, 2020). Observational data can then be used to validate the reliability of model outputs.…”
Section: Introductionmentioning
confidence: 99%
“…The 14-class and 1 km spatial resolution land cover map generated by [25] was used to obtain a vegetation type map, which was used to simulate GPP (Section 2.3). Elevation extracted from the Shuttle Radar Topography Mission 3 arc second digital elevation model [26] and land cover data from the Spanish Land Use Information System (SIOSE) [27] were combined to obtain a forest type map [28], which was used to simulate forest respiration (Section 2.4).…”
Section: Vegetation and Forest Type Mapsmentioning
confidence: 99%